2021
DOI: 10.1002/ldr.4022
|View full text |Cite
|
Sign up to set email alerts
|

Shift in archaeal community along a soil profile in coastal wheat‐maize rotation fields of different reclamation ages

Abstract: Coastal mudflats reclamation activities show a strong influence on soil properties and microbial community activity, which drive soil carbon and nitrogen cycling. Studies have found there is a shift of bacterial community with reclamation time. However, effects of reclamation time on the soil archaeal community are still largely unknown.Here, we determined soil properties and archaeal community in the soil profiles (0-15, 15-30, 30-45 cm) of different reclaimed sites with different reclamation ages (R12: 12-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…pH positively impacted on the relative abundance of Nitrosopumilaceae and Thermoplasmata, which dominated in DW and sediment samples with a pH of 7.76-8.35 (Figure 3A). The relationship between Nitrosopumilaceae and pH was consistent with those observed in farmland soils and saline soils (Wan et al, 2021;Wang B. et al, 2022). The relative abundance of Thermoplasmata was reported negatively correlated with pH in acidic tropic soil, acidic springs, solfataras, and volcanic soils (Tripathi et al, 2013), whereas an opposite correlation was observed in our alkaline cave.…”
Section: Different Response Of Prokaryotic Communities To Environment...supporting
confidence: 87%
See 1 more Smart Citation
“…pH positively impacted on the relative abundance of Nitrosopumilaceae and Thermoplasmata, which dominated in DW and sediment samples with a pH of 7.76-8.35 (Figure 3A). The relationship between Nitrosopumilaceae and pH was consistent with those observed in farmland soils and saline soils (Wan et al, 2021;Wang B. et al, 2022). The relative abundance of Thermoplasmata was reported negatively correlated with pH in acidic tropic soil, acidic springs, solfataras, and volcanic soils (Tripathi et al, 2013), whereas an opposite correlation was observed in our alkaline cave.…”
Section: Different Response Of Prokaryotic Communities To Environment...supporting
confidence: 87%
“…Nitrosopumilaceae preferred aquatic niches (DW) in the Heshang Cave, which might process ammonia-oxidation in water samples (Toumi et al, 2021). Aenigmarchaeales, found in ice-capped lake and wheat-maize rotation soils, has never been reported in karst ecosystem (Wan et al, 2021;Vigneron et al, 2022). Nevertheless, low abundance of Aenigmarchaeales was found in DW samples (0.31 ± 0.33%), especially in DW1 with high metabolic potential in summer (Yun et al, 2018).…”
Section: Microbial Functional Inference and Ecological Trait Assignme...mentioning
confidence: 99%
“…This superphylum includes a variety of still poorly characterized small-sized microorganisms with diverse metabolic features that are supposed to be widespread in the environment (Moissl-Eichinger et al 2018 ). The presence of DPANN in agricultural soils, including rice paddies, was recently reported, however, without further discussion (Wan et al 2021 , Cho et al 2022 ). Members of the phylum Nanoarchaeota include putative sulfide-oxidizers that live as obligate endosymbionts of Crenarchaeota (St. John et al 2019 ), and might play a crucial role in sulfur cycling in rice paddies and in plant detoxification from reduced sulfur compounds.…”
Section: Discussionmentioning
confidence: 98%
“…Crenarchaeota, and Thermoplasmatota were the predominant archaeal phyla in the −FN and +FN treatments. These phyla are associated with nitrogen cycling (Nitrosopumilaceae, Nitrososphaeraceae, and Nitrosotaleaceae) ( Wan et al, 2021 ), and carbon metabolism (Marine Group I) ( Swan et al, 2014 ). Intriguingly, a noticeable reduction in Nitrosotaleaceae ( Candidatus Nitrosotalea ) and Nitrososphaeraceae was observed in pre-sterilized rhizosphere soil.…”
Section: Discussionmentioning
confidence: 99%